2021
DOI: 10.32604/cmc.2021.012200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Behaviors of Nonlinear Coronavirus (COVID 9) Model with Numerical Studies

Abstract: The development of mathematical modeling of infectious diseases is a key research area in various elds including ecology and epidemiology. One aim of these models is to understand the dynamics of behavior in infectious diseases. For the new strain of coronavirus (COVID-19), there is no vaccine to protect people and to prevent its spread so far. Instead, control strategies associated with health care, such as social distancing, quarantine, travel restrictions, can be adopted to control the pandemic of COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…This is because that DNA is a long object 7 meters long which is compacted in less than micrometers. Thus, this system could be similar to a black string with the below metric [9][10][11][12][13][14][15][16][17][18][19][20][21][22]:…”
Section: A Quantum Model For Exchanging Waves Between Bacterial and Cellular Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…This is because that DNA is a long object 7 meters long which is compacted in less than micrometers. Thus, this system could be similar to a black string with the below metric [9][10][11][12][13][14][15][16][17][18][19][20][21][22]:…”
Section: A Quantum Model For Exchanging Waves Between Bacterial and Cellular Dnamentioning
confidence: 99%
“…Fractional order differential equations (FDEs) are usually used to model systems that have a memory that occurs in sundry physical phenomenas, models in the thermoelasticity field, and biological ideals see ( [9][10][11], [12][13][14], [15][16][17], [18][19][20], [21][22][23], [24][25][26], [27][28][29], [30][31][32]).…”
Section: Introductionmentioning
confidence: 99%
“…Over the most recent couple of years, various numerical models have been created to give smart subtleties into numerous issues of interest including the transmission and control of irresistible illnesses [1][2][3]. The description of the ongoing pandemic of Coronavirus, as viral pneumonia in late 2019 in Wuhan-China which has spread worldwide across 210 countries is "SARS-CoV-2" [4][5][6]. It is seething around the world with a tremendous cost as far as human, financial, and social effects [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Alotaibi et al [ 28 ] investigated solution of COVID -19 model, and they concluded that homotopy annoyance and decreased differential change techniques are adequate for solving such model equations. Modified reduced differential transform and homotopy perturbation method have also been used in some other researches [ 29 , 30 ]. In the research of Mahdy et al [ 31 ], they investigated Rubella ailment disease model using shifted second-order Chebyshev polynomials type which they claimed had not been used before and concluded that the method is efficient and its simple-to-use style makes it suitable for finding convergent solutions to Rubella disease models.…”
Section: Introductionmentioning
confidence: 99%